Post-industrial future of Belarus: threat and imperatives - Orgish, Viachaslau P. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
In the article, the most acute crisis of the socio-economic and political institutions of the national state is the subject of consideration, due to the phase transition from the industrial mode of production to the cognitive (post-industrial) mode. The thesis is opened that in the era of globalization the national state inevitably faces threats from transnational structures. The economic and social challenges that Belarus expects in the process of post-industrial transformation are analyzed.
Keywords: post-industrialism; corporatocracy; modernization of the national economy; global actors; transnational elites